Pengembangan Kemandirian Remaja terhadap Manajemen Dismenorea dengan Ekstrak Majeniku di Desa Sembulang Kec. Galang - Purba, Netty Herawaty; Maisyaroh UP, Septi; Fransiska Pakpahan, Yohana; Oktavia Samosir, Yossi (LPPM Akbid Harapan Ibu Pekalongan, 2025)
Dysmenorrhea is a common condition and refers to painful menstruation (periods) with severe cramps affecting the lower abdomen. The pain starts a few hours before or with the onset of menstruation and lasts for 1-3 days. Pain and frequency may decrease with age or after childbirth. Research shows that between 41% - 91.5% of young women, school and college age, experience dysmenorrhea. Lifestyle changes include aerobic exercise and stretching, while complementary alternative treatments include peppermint, cinnamon, ginger and other herbs and supplements. This activity is a continuation of research that has been conducted. Based on the above background, researchers are interested in conducting community service activities with the title Development of Adolescent Independence on Dysmenorrhea Management with Majeniku Extract in Sembulang Village, Galang Kec. With the method of empowering adolescents in processing Majeniku. The initial activity was an exploration with a field survey, and coordination with the Head of Sembulang Village, Sub district galang In the service activity before the activity begins the community service team conducts the Pre-test stage, counseling, discussion and making Majeniku, at the counseling stage the activity is carried out, making Majeniku extracts involving teenagers who are present. Post-test and evaluation stages receive feedback responses from participants to the community service team.